2021
DOI: 10.1002/joec.12156
|View full text |Cite
|
Sign up to set email alerts
|

Career Services in the Post‐COVID‐19 Era: A Paradigm for Career Counseling Unemployed Individuals

Abstract: The 2019 novel coronavirus (COVID‐19) pandemic has caused unprecedented economic disruption and unemployment worldwide, threatening to become both a financial and a humanitarian crisis. Prolonged labor market recession and an acute rise of unemployment are expected. The main question for career counselors will be how to provide effective career counseling to unemployed people in the post‐COVID‐19 world, where they may face many other unemployment‐related problems. In this article, we suggest application of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Job loss can be viewed by individuals as a time for self‐evaluation as they reframe lifestyle decision‐making and confront long‐term aftereffects of personal stagnation and loneliness. The results of this study resonate with emerging literature suggesting that COVID‐19 unemployment contributes to people feeling sad and unjustly treated (Akkermans et al, 2020 ; Drosos et al, 2021 ). Despite the complexities associated with recovery from unemployment, people from economically marginalized environments found reconnections with family, moments of gratitude, and eventual acceptance of a collective new norm.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Job loss can be viewed by individuals as a time for self‐evaluation as they reframe lifestyle decision‐making and confront long‐term aftereffects of personal stagnation and loneliness. The results of this study resonate with emerging literature suggesting that COVID‐19 unemployment contributes to people feeling sad and unjustly treated (Akkermans et al, 2020 ; Drosos et al, 2021 ). Despite the complexities associated with recovery from unemployment, people from economically marginalized environments found reconnections with family, moments of gratitude, and eventual acceptance of a collective new norm.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding job replacement, a few participants recognized they needed additional support from outside organizations relating to job search and future career development. Research has shown that efforts to find new employment are often unsuccessful because of the lack of job‐hunting skills; however, career interventions have been found to increase one's self‐efficacy and overall confidence toward job search (Drosos et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations